2018
DOI: 10.1002/adhm.201801139
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Stimulation by an Organic Transistor Architecture Induces Calcium Signaling in Nonexcitable Brain Cells

Abstract: materialsdisplay intrinsic multi functionality, combining ionoelectronic transport properties, photonic properties, and optical transparency within the visible range with improved biocompatibility with neural cells compared to inorganic sub strates. [1][2][3][4] Notably, the survival of primary neuronal cells on organic bioelectronic polymers [1,3,4] and small molecules [5,6] is higher when compared to silicon/glass substrates, while the functionality of brain cells is preserved on organic biofunctional interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 61 publications
1
23
0
Order By: Relevance
“…To date, extracellular recording systems based on planar microelectrode arrays (MEAs) are the optimal electrophysiological equipment for noninvasive long‐term analysis studying of neuronal circuit‐connectivity in vitro and in vivo 7. While stimulation of astrocytes signaling has been achieved successfully with organic field effect transistor devices, the use of MEA for the recording of astroglial cells signaling in vitro still displayed critical issues 8–10. First, astrocyte primary cultures, grown on flat substrates lose structural and functional features,11a,b,12 essential for their homeostatic and physiological function in vivo 13.…”
Section: Introductionmentioning
confidence: 99%
“…To date, extracellular recording systems based on planar microelectrode arrays (MEAs) are the optimal electrophysiological equipment for noninvasive long‐term analysis studying of neuronal circuit‐connectivity in vitro and in vivo 7. While stimulation of astrocytes signaling has been achieved successfully with organic field effect transistor devices, the use of MEA for the recording of astroglial cells signaling in vitro still displayed critical issues 8–10. First, astrocyte primary cultures, grown on flat substrates lose structural and functional features,11a,b,12 essential for their homeostatic and physiological function in vivo 13.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently demonstrated that it is possible to evoke astrocytic Ca2+ responses mediated by TRPV4, TRPA1 as well as cell swelling with electrical stimulation 21 by organic cell stimulating and sensing device. Previous attempts from other groups to evoke astrocytic Ca 2+ responses with light in cell cultures were only successful when used with cell‐conjugated NIR‐optimized plasmonic nanostructures or label‐free with high‐intensity ultrafast NIR laser pulses 56‐58 .…”
Section: Discussionmentioning
confidence: 99%
“…Methods to study astrocytic processes have been for a long time confined to conventional pharmacology, genetic manipulation, fluorescence imaging of molecular sensors, and electrophysiology 3,5,11,14,17‐19 . More recently, we demonstrated that it is possible to evoke chloride ion conductances, 20 astrocytic Ca2+ responses mediated by TRPV4 and cell swelling by optical or electrical stimulation operated by organic devices 21 . Optical tools can provide precise, fast, label‐free control of ions, and water dynamics to study the cellular and molecular mechanisms of astrocytes function and to potentially treat dysfunction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among small molecule organic semiconductors, perylene dimmide derivative N, N'-ditridecylperylene-3,4,9,10tetracarboxylic diimide (P13), has been shown to be biocompatible with rat primary astrocytes in vitro. [114] In a recent work, it is shown that transparent organic cell stimulating and sensing transistor (O-CST) architecture, fabricated with P13, [115] was used to explore the impact of field effect extracellular stimulation on intracellular calcium concentration ([Ca 2+ ] i ) in primary rat neocortical astrocytes. Calcium imaging experiments enabled by the transparency of O-CST showing that a slow rise in extracellular potential between the gate and the grounded source electrodes provide an effective extracellular electrical stimulation of astrocytes that induces a slow and persistent increase in astrocytic [Ca 2+ ] i .…”
Section: Organic Bioelectronic and Optoelectronic Glial Interfacesmentioning
confidence: 99%